2009
DOI: 10.1016/j.jssc.2009.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of ALnO2 (A=Cu or Ag; Ln=rare earths) with the delafossite structure

Abstract: Synthesis, structures, and magnetic properties of ternary rare earth oxides ALnO 2 (A = Cu or Ag; Ln = rare earths) have been investigated. CuLnO 2 (Ln = La, Pr, Nd, Sm, Eu) were synthesized by the direct solid state reaction of Cu 2 O and Ln 2 O 3 , and AgLnO 2 (Ln = Tm, Yb, Lu) were obtained by the cation-exchange reaction of NaLnO 2 and AgNO 3 in a KNO 3 flux.These compounds crystallized in the delafossite-type structure with the rhombohedral 3R type (space group: R-3m). Magnetic susceptibility measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…At low temperatures, we observed a large χ 0 value, which includes the Van-Vleck susceptibility χ VV , arising from CEF excitations [41]. Such a large low-temperature χ VV contribution is typical for Yb-based compounds [16,42].…”
mentioning
confidence: 63%
“…At low temperatures, we observed a large χ 0 value, which includes the Van-Vleck susceptibility χ VV , arising from CEF excitations [41]. Such a large low-temperature χ VV contribution is typical for Yb-based compounds [16,42].…”
mentioning
confidence: 63%
“…Inspired by the works of YbMgGaO 4 , recently another large family of rare‐earth triangular antiferromagnets, ARX 2 (space group: R‐3m ), had been extensively studied as well, where A + = Ag + , Na + , R 3+ = rare‐earth ions, and X 2− = O 2− , S 2− , Se 2− . Among them, NaYbS 2 and NaYbO 2 have captured most special interest.…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%
“…Cu-based delafossites have attracted attention due to their expected large hole mobility, a result of the mixing of Cu 3d and O 2p states forming the valence band. It has been reported that this delafossite structure allows the hosting of a multitude of M cations, namely p-block elements (Al [49,103,104], B [105][106][107], Ga [54,108,109] or In [110][111][112][113]), transition metals (Co [114,115], Cr [82,116,117], Fe [118][119][120], Mn [121,122], Rh [123], Sc [124][125][126] and Y [89,[126][127][128]), or lanthanides (La [129][130][131], Nd [132], Pr [133], Sm and Eu [134]). These materials were thoroughly investigated as they demonstrated interesting properties in the different fields: antibacterial [135,136], batteries [137], (photo)catalyse [83,131,[138][139][140], lumine...…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%